A Convenient Method for α‐Chlorination of 1, 3‐Diketones and β‐Keto Esters with DMSO or Ph2SO/(COCl)2. Issue 40 (25th October 2021) - Xi, Zeyu; Liu, Yuanjian; Wang, Hao; Guan, Di; Liu, Yongguo; Sun, Baoguo; Tian, Hongyu; Liang, Sen
Abstract: It has been found that the monochlorination of most of 1, 3‐diketones and β‐ketoesters under investigation can be achieved using DMSO or Ph2 SO/(COCl)2 at −20∼0 °C in moderate to high yields. The 1, 3‐diketones, which enol forms are stabilized by an intramolecular hydrogen bond, bulky β‐ketoesters, and α‐monoalkylated 1, 3‐dicarbonyls undergo chlorination well with DMSO/(COCl)2, whereas the chlorination of the less bulky β‐ketoesters needs Ph2 SO/(COCl)2 instead. The chlorodimethylsulfonium salt or chlorodiphenylsulfonium salt generated by the reaction of DMSO or Ph2 SO with (COCl)2 is proposed as a Cl + source for chlorination, which provides a convenient access to the monochlorination of 1, 3‐dicarbonyls. Abstract : The monochlorination of 1, 3‐dicarbonyls can be achieved using DMSO or Ph2 SO/(COCl)2 at −20∼0 °C in moderate to high yields. The chlorodimethylsulfonium salt or chlorodiphenylsulfonium salt generated by the reaction of DMSO or Ph2 SO with (COCl)2 is proposed as a Cl + source for chlorination.